Tantangan dan Peluang Budaya Lokal Dalam Misi Pemberitaan Injil - Sicilia Sima; Jepriadi Jepriadi; Sulianus Susanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2022)
Culture is something that cannot be separated from human life. On the other hand, culture is an inseparable part of humans in their totality. There are various cultures in the world and they are local to certain communities. This is the fact that Christians face in carrying out their mission of preaching the Gospel with various difficulties. However, there are opportunities that can become a way of spreading the Gospel, because cultures have points of contact that can be a way of connecting one another. In that case opportunities for preaching the Gospel can be made possible. The method used in this research is the library research method. The results of this research are that, to carry out the mission of preaching the Gospel in local culture, a Gospel preacher must be able to understand the local language and culture, and be able to contextualize it with the social life of the local community.